Northwest History. Forest Fires (Cont'd). (1936)
Ten Forest Blazes Quelled By Crews: Clearwater Timber Protective Association Area Relatively Free From Smokes-Push Maintenance Work. Ten Forest Blazes Quelled By Crews: Clearwater Timber Protective Association Area Relatively Free From Smokes-Push Maintenance Work. Headquarters, June 29.—Ten small woods fires last week brought the total up to 11 for the 1936 season in the Clearwater Timber Protective association area, the weekly summary by A. B. Curtis, state fire warden, showed. Seven of last week's fires were holdovers from brush burning and three were started by the electrical storms. Three-fourths acre of slashings were burned. Regular fire season employees on duty numbered 26, the report said. Three lookout points are being used. Labor conditions were termed favorable. Only a trace of rain was recorded in the storm period that effectively damped forest reserves. The temperature reading on Monday was 98, near the high mark for Headquarters. Work on Beaver creek lookout, Bradford cabin and Lolo trail road projects is underway. Work was also in progress on Harlan cabin, Beaver creek road and Shanghai lookout. CCC enrollees are employed on the projects. Trails are about 75 per cent cutout. Telephone lines were in bad condition with repairs taking more time than usual.